Physical and Chemical Characteristics of Well and Groundwater) - SOOTKONGTHONG, Koonphet; HAPBOUALY, Phanomxay; SAIYALARD, Sengchanh; KONGMANY, Santi (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The physical and chemical characteristics of well and groundwater at Soukhuma District of Champasack Province started in dry and rainy season. It’s collected 5 sampling point each point was 3 replications. Which the water samples contained in a 1500 ml bottle with 2–3 drops of sulfuric acid and nitric acid then soak into ice bucket to preserved its original characteristics. After that, filter sample from the field into a beaker with filter paper and pour into a vial for examined by 8 parameters: Acidity-Base (pH) by using a pH meter SD300pH, Electrical Conductivity (EC) by using a Conductivity meter AL20Con and Total Alkalinity, Calcium (Ca2+), Manganese (Mn2+), Sulfate (SO42-), Sulfide (S-) and Ferrous II ion (Fe2+) by using a Photo meter MD600. The research result founded that: In the dry season, pH value of well is lower than the standard value at almost all points, Manganese of well at T2 is higher than the standard value, Sulfide of well at T1 is higher than the standard value, for EC, Calcium, Sulfate and Ferrous II ion are all standard. pH of well in rainy season is lower than the standard value at almost all points (for other parameters are within the standard at all point). pH of groundwater in dry season at T3 is lower than the standard value, EC of groundwater at T1 and T5 is higher than the standard value, Total Alkalinity of groundwater at T4 is higher than the standard value, Calcium and manganese of groundwater at T5 is higher than the standard value. for Sulfate, Sulfide and Ferrous II ion are all standard. In the rainy season, pH value of groundwater at T1, T2 and T3 is lower than the standard value, EC of groundwater at T1 is higher than the standard value, Total Alkalinity of groundwater at T4 is higher than the standard value, Sulfate of groundwater at T1 and T5 is higher than the standard value, Sulfide of groundwater at T1 is higher than the standard value. For Calcium, Manganese and Ferrous II ion are all standard. In conclusion, the wells and the groundwater have not yet passed the national environment standards. Since it was contaminated with chemicals and posed a risk to the health safety of people in the areas. However, this research is only a basic.